2019
DOI: 10.1039/c9nr06078b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic manganese oxide nanostructures for the reverse water gas shift reaction

Abstract: We develop efficient synthetic methods to prepare various MnO2 structures and investigate their structure–property relationships as applied to the reverse Water Gas Shift (rWGS) reaction with a combination of experimental and theoretical tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 58 publications
1
45
1
Order By: Relevance
“…It is worth mentioning that, based on similar HRTEM results of MnO 2 nanowires along their radial direction, previous studies have directly ascribed the observed planes to be the exposed outmost facets and to be further responsible for specific functional properties. [ 13,22,23,25,28–31,33–35,42–46 ] Without direct axial imaging, the deduction of exposed lateral facets solely based on radial TEM imaging in these studies could be plagued by the random sample orientation and the unknown cross‐sectional shape of the nanowires. We further corroborate this statement as later discussed in Figure 4 showing the axial imaging of α‐MnO 2 nanowire, where α‐(310) planes observed via radial TEM imaging in Figure S1, Supporting Information, are not actually seen as the exposed lateral facets.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that, based on similar HRTEM results of MnO 2 nanowires along their radial direction, previous studies have directly ascribed the observed planes to be the exposed outmost facets and to be further responsible for specific functional properties. [ 13,22,23,25,28–31,33–35,42–46 ] Without direct axial imaging, the deduction of exposed lateral facets solely based on radial TEM imaging in these studies could be plagued by the random sample orientation and the unknown cross‐sectional shape of the nanowires. We further corroborate this statement as later discussed in Figure 4 showing the axial imaging of α‐MnO 2 nanowire, where α‐(310) planes observed via radial TEM imaging in Figure S1, Supporting Information, are not actually seen as the exposed lateral facets.…”
Section: Resultsmentioning
confidence: 99%
“…He et al. recently demonstrated ideal selectivity on nanostructured MnO 2 catalyst at 1 : 1 H 2 : CO 2 thermally stable up to 850 °C at ambient pressure [22] …”
Section: Figurementioning
confidence: 99%
“…Methanation active catalysts, such as Ni, Ru, or Rh generally have a lower activation energy for the RWGS reaction that combined with higher metal loadings and high temperature operation yields conversion rates orders of magnitude higher than WGS selective catalyst [19, 22–26] . Byproduct formation of methane can be converted to CO at high temperatures through the steam methane reforming reaction (reverse methanation, Reaction 2) to obtain a desirable H 2 /CO ratio and low or negligible methane content for subsequent processes [27] .…”
Section: Figurementioning
confidence: 99%
“…In recent decades, heterogeneous catalysts that promote the RWGSR have been extensively studied because of the gradual realization of their widespread application prospects for CO 2 utilization. At the early stage, much research has focused on the oxide catalysts due to their effluent oxygen vacancies sites, such as CeO 2 , CuO, ZnO, Al 2 O 3 , Fe 2 O 3 , Cr 2 O 3 , In 2 O 3 , and MnO 2 (Saeidi et al, 2017 ; Su et al, 2017 ; He et al, 2019 ). Although the CO selectivities of these oxide catalysts are desirable in RWGSR, their disadvantages of lower CO 2 activation and feasible poisons and sintering are hindering their extended application.…”
Section: Catalytic Systemmentioning
confidence: 99%